The Effect of Health Education Using Leaflet Media on Mother’s Knowledge About Exclusive Breastfeeding: A Quasi-Experimental Study - Desmawati, Elis; Putri, Nesa Ayu Murthisari (Lentera Perawat, 2025)
Exclusive breastfeeding for the first six months has been proven to be important for maternal and infant health. However, the coverage of exclusive breastfeeding in Indonesia is still low. Data shows that coverage in Indonesia is only 65.8% below the target of 80%. One of the main causes is the lack of knowledge of mothers about the benefits of exclusive breastfeeding. For this reason, education that is easy to access and understand, such as leaflets, is needed. Leaflets are considered effective because they are practical, can be reread at any time, and are very helpful for mothers in areas with limited digital technology. This study aims to determine the effect of counseling using leaflets on increasing maternal knowledge about exclusive breastfeeding. The research design used was a quasi-experimental with a one group pre-post test approach. A total of 31 mothers who had babies aged 0–24 months were involved as respondents selected using a purposive sampling technique. This technique was used because researchers needed subjects who specifically met the inclusion criteria, namely having babies in that age range, being present during the activity, and being willing to take part in the entire series of studies. This study has obtained ethical approval from the relevant institutions. The research instrument was a questionnaire that had been validated and proven to be reliable. The Wilcoxon test results showed a significant increase in knowledge from 51.61% to 93.33% (p < 0.000), indicating that the leaflet is effective as an educational medium. Although this study is limited to the number of respondents and location, the results provide an illustration that leaflets if well designed and delivered by health workers can be a powerful communication tool in supporting exclusive breastfeeding.